Digital-Facial Translocation in Amniotic Band Sequence: Evidence of the Intrinsic Theory. Issue 7 (October 2018) - Weinstein, Brielle; Hassouba, Mahmoud; Flores, Roberto L.; Staffenberg, David A.; Gordon, Christopher B.; Runyan, Christopher M.
Abstract : Abstract: Amniotic band sequence is a complex congenital anomaly in which infants with typically no known genetic mutation have bands of maternal amniotic tissue wrapped around body parts, most commonly the limbs and digits. The authors report a novel variation on this presentation in 3 patients from 2 centers with complex craniofacial clefting and amniotic band sequence. They presented with hypertelorism, different forms of complex craniofacial clefting, and bands connecting ipsilateral hands to facial clefts, with digital-facial translocation in 2 cases. These findings support a model in which complex craniofacial clefts result in areas of exposed, sticky, and temporally and spatially coincident mesenchyme within the embryo that are susceptible to adherence of ipsilateral fetal hands. This strongly supports the intrinsic and adhesion theories of the etiology of amniotic band syndrome.